Cordyceps militaris extracts and cordycepin ameliorate type 2 diabetes mellitus by modulating the gut microbiota and metabolites - Xinyuan Liu; Mengqian Dun; Tongtong Jian; Yuqing Sun; Mingyu Wang; Guoying Zhang; Jianya Ling (Frontiers Media S.A., 2023)
Introduction:Cordyceps militaris, which has many potential medicinal properties, has rarely been reported to alleviate type 2 diabetes mellitus (T2DM).Methods: The effects of C. militaris extracts (CE) and cordycepin (CCS) on high-fat diet and streptozotocin (STZ) induced T2DM mice were analysed by gut microbiome and metabolomics methods in this study.Results: The results demonstrated that glucose and lipid metabolism parameters, oxidative stress biomarkers and inflammation cytokines were down-regulated in the CCS and CE groups. A comparative analysis of the fecal samples from mice in the model and experimental groups showed that experimental groups resulted in a higher abundance of Firmicutes/Bacteroidetes.Conclusion: This study provides evidence that C. militaris can be used as a food supplement to relieve T2DM, which provides a promising prospect for new functional food in it.